Severe cerebral congophilic angiopathy coincident with increased brain aluminium in a resident of Camelford, Cornwall, UK. Issue 7 (20th April 2006) - Exley, C; Esiri, M M
Abstract : In July 1988, 20 tonnes of aluminium sulphate was discharged by the South West Water Authority into the drinking water supplied to a large region of North Cornwall. Up to 20 000 people were exposed to concentrations of aluminium which were 500–3000 times the acceptable limit under European Union legislation (0.200 mg/l). Although this incident is currently the topic of a government inquiry, nothing is known about its longer-term repercussions on human health. The first neuropathological examination of a person who was exposed and died of an unspecified neurological condition was carried out. A rare form of sporadic early-onset β amyloid angiopathy in cerebral cortical and leptomeningeal vessels, and in leptomeningeal vessels over the cerebellum was identified. In addition, high concentrations of aluminium were found coincident with the severely affected regions of the cortex. Although the presence of aluminium is highly unlikely to be adventitious, determining its role in the observed neuropathology is impossible. A clearer understanding of aluminium's role in this rare form of Alzheimer's related disease should be provided by future research on other people from the exposed population as well as similar neuropathologies in people within or outside this group.